Analisis Perilaku Konsumen Dan Produk Terhadap Keputusan Pembelian Salad Nyoo Daerah Istimewa Yogyakarta (DIY) Analysis Of Consumer And Product Behavior On The Purchasing Decisions Of Salad Nyo Daerah Istimewa Yogyakarta (DIY) - Ratnaningtyas, Endah Marendah; Paays, Nadya Fransisca; Jumadi, Jumadi (EBBANK, 2023)
Salad are becoming more and more popular among Indonesian because of their high nutritional contect and ease of preparation. Salad Nyo is one of the salad products circulating in the market with various variants and services. This research aims to analyze the influence of consumer behavior and products on the decision to purchase Salad Nyo. The method used by the researcher is a survey by distributing questionnaires to 100 respondents who are consumers of Salad Nyo products located in the Special Region of Yogyakarta. Data analysis using the multiple regression method multiple regression, t test and f test.Based on the research result it is known that consumer and product behavior has a significant effect on purchasing decisions of Salad Nyo Spesial Region of Yogyakarta (DIY) and the result of the determination test show 0,629 so that the consumer and product behavior variable is 38.3% which is able to explain the purchase decision variable while the remaining 61.7% influenced by other factors not examined